Pelatihan Perilaku Hidup Sehat Pada Siswa Sekolah Luar Biasa Negeri Jember - Banun Kusumawardani; Dwi Merry Christmarini Robin; Yani Corvianindya Rahayu; Parawita Dewanti; Siti Komariyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Healthy living behavior training is an effort to empower students of SLB Negeri Jember. The implementation of the training has been designed according to the abilities of the students. This activity has implemented the concept of improving life skills so that students are prevented from various diseases and are able to live healthy independently. The implementation method is as follows: 1) counseling and training on healthy living behavior and brushing teeth properly; 2) general health and oral health examinations; and 3) revitalization of School Health Unit through training of Student Health Cadres. Activities are equipped with modules and health examination record books. Activity evaluation procedures include: 1) re-examination of general health status; 2) re-examination of oral health status; and 3) supervision one month after program implementation. At the end of the activity, the students are able to wash their hands and brush their teeth properly and independently. Student Health Cadres are able to take measurements of height, weight, and body temperature. The general health profile of students is quite good, but their oral health is still poor and requires treatment from health workers.